"This one is a bit of a taboo subject": a mixed methods investigation into the impact of head and neck cancer upon sexuality - McCabe-White, Linda (2022)
Background: Previous research demonstrates Head and Neck Cancer (HNC) survivors are vulnerable to a negatively impacted sexuality although it is unclear whether changes are attributable to HNC sequelae or other (e.g. maturation) factors. Sexuality is important to wellbeing and unmet sexuality needs following cancer can increase psychological distress. Gaps in knowledge surround the impact of HNC on sexuality: there is considerably less research in relation to HNC’s impact on sexuality in comparison to other cancers.This is surprising as HNC is the seventh most common cancer and can produce various functional, aesthetic, and psychosocial difficulties. Individual differences in coping/response style account for variability in experiences of living with cancer – there are links between particular coping styles and levels of psychological distress which could be explored in relation to sexuality outcomes. These differences can be targeted through psychological intervention in ways that clinical or demographic characteristics cannot be. Additionally, professionals struggle to discuss sexuality, meaning that the perceived support needs for physical, practical, and psychological support around sexuality are not fully known.